A CASE OF CORNUAL ECTOPIC PREGNANCY THAT WAS SUCCESFULLY LAPAROSCOPICALLY TREATED - Georgiev, Dimitar; Ismaili, Bashkim; Tahir, Shenol; Kocevska, Ana; Skeparovska, Kristina (Journal of Morphological Sciences; Vol 5 No 1 (2022): JMS, 2022)
Cornual pregnancy is a rare type of ectopic pregnancy where the embryo implants in the junction between the fallopian tube and the uterus. Only 2% to 3% of all tubal pregnancies are cornual. Uterine rupture may occur in up to 20% of the cases of cornual pregnancy that progress beyond 12 weeks of amenorrhea, resulting in massive hemorrhage due to high vascularity in this region through the branches of the uterine artery. Despite the availability of modern diagnostic modalities including transvaginal ultrasonography, there is difficulty in the early diagnosis because of its location. We present a case of unruptured cornual ectopic pregnancy in a 40-year- old woman with amenorrhea of 7 weeks. In our case, the diagnosis was made early and laparoscopic cornuostomy with removal of the gestational sac and ipsilateral salpingectomy were performed, followed by laparoscopic repair of the cornuostomy incision. Hemostasis was achieved with electrocoagulation. This caused minimal hemorrhage without intraoperative and postoperative complications. Keywords: cornual pregnancy, ectopic pregnancy, transvaginal ultrasonography, laparoscopic cornuostomy. https://doi.org/10.55302/JMS2251039g